Metabolic Comorbidities in Pediatric Psoriasis-A Comparative Cross-Sectional Study in South-Asian Children - Ranjana E. Joseph; Dharshini Sathishkumar; Ankan Gupta; Sophy Korula (Wolters Kluwer Medknow Publications, 2024)
Background: There is only limited data on the association between psoriasis and metabolic comorbidities in South-Asian children. Objective: To examine metabolic comorbidities among South-Asian children with and without psoriasis. Materials and Methods: A hospital-based, comparative, cross-sectional study was conducted in children with and without psoriasis over 19 months. Anthropometric, clinical, and metabolic comorbidity details (including disease extent and severity scores, obesity, systemic hypertension, diabetes mellitus, lipid abnormalities, and metabolic syndrome) were obtained in both groups according to standard criteria. Results: Fifty-eight children with psoriasis (25 males/33 females, age 11.3 ± 3.0 years, range 4 to 17 years) and 62 children without psoriasis (37 males/25 females, age 11.0 ± 3.6 years, range 4 to 18 years) were recruited. The prevalence of obesity (31.0% versus 14.5%, P = 0.031, odds ratio 2.65) and metabolic syndrome (18.6% versus 4.6%, P = 0.044, odds ratio 4.68) were higher in children with psoriasis than without. The prevalence of other metabolic comorbidities (systemic hypertension, pre-diabetes, lipid abnormalities, elevated serum alanine aminotransferase, and non-alcoholic fatty liver disease) was not different between children with and without psoriasis and between obese and non-obese children with psoriasis. Among children with psoriasis, those with abdominal obesity had significantly lower disease severity and extent scores than those without. Conclusion: Psoriasis is associated with a significantly higher prevalence of obesity and close to significantly higher prevalence of metabolic syndrome in South-Asian children. Screening for metabolic comorbidities is essential even in non-obese children with psoriasis. Disease extent and severity are less in obese compared to non-obese South-Asian children with psoriasis.